Narrative approaches to the morality of persons with antisocial personalities: some philosophical considerations - Luca Malatesti; Iris Vidmar Jovanović (Diacovensia, 2025)
From a philosophical perspective, we investigate some conceptual and methodological issues concerning the narrative approach in studying the moral understanding and reasoning of individuals with antisocial personalities and psychopathy. We deal with two kinds of issues: those relating to the epistemic and referential status of narratives in general and psychotherapeutic narratives in particular; and those relating to the role that narrative can have in scholarly engagements with mental disorders. Although we do not decide on the ultimate empirical validity and fruitfulness of data gathered using these narrative approaches, we defend philosophically their plausibility and support the further development of these methods and their application to studying the “moral landscape” of individuals with antisocial personality disorder.